Biochemical and inhibitor analysis of recombinant cellobiohydrolases from Phanerochaete chrysosporium - Bianca Oliva; André Ferraz; Fernando Segato (Biotechnology for Biofuels and Bioproducts)
Abstract The demand for greener energy sources necessitates the development of more efficient processes. Lignocellulosic biomass holds significant potential for biofuels production, but improvements in its enzymatic degradation are required to mitigate the susceptibility of enzymes by reaction products and pretreatment impurities. In this work, two cellobiohydrolases (CBHs) from the basidiomycete Phanerochaete chrysosporium (PcCel7C and PcCel7D) were heterologously expressed, characterized, and analyzed in the presence of their products (glucose and cellobiose) and harmful compounds commonly found in industrial processes (phenolics), as well as their adsorption to lignin and cellulose. The enzymes exhibited an optimum temperature of 55 °C and displayed a pH profile similar to the model CBHI from Trichoderma reesei (TrCel7A). Activity decreased consistently for all CBHs in the presence of cellobiose, while glucose significantly impacted the basidiomycete CBHs. Phenolic compounds with a higher content of OH groups were found to be more detrimental to the enzymes, with the location of the OH group on the phenolic ring playing a crucial role in enzyme deactivation. Molecular docking simulations predicted that the product-binding site of CBHs has the highest affinity for interaction with phenolics; however, they are unlikely to interact at this site in the presence of substrate. PcCel7C and PcCel7D exhibited poorer adsorption on cellulose compared to the TrCel7A enzyme. These findings provide insights into how the structure of CBHs influences their susceptibility to inhibitors and deactivating compounds present in saccharification reaction medium.